2007
DOI: 10.1177/1477153507080922
|View full text |Cite
|
Sign up to set email alerts
|

Mesopic visual efficiency III: Discrimination threshold measurements

Abstract: The authors represent a research consortium which has adopted a task performance based approach for nighttime driving to obtain mesopic spectral sensitivity functions. This study describes investigations based on discrimination threshold techniques and compares the results with those obtained from detection threshold measurements. It forms a continuation of `Mesopic models — from brightness matching to visual performance in night-time driving: a review'. 1 The achromatic increment contrast threshold for discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 12 publications
1
22
0
2
Order By: Relevance
“…54 The mesopic system was derived from two parallel bodies of work, the European MOVE consortium [55][56][57][58] who used and driving on a test track. 62 The mesopic visual response is essentially a weighed combination of the scotopic (S) and photopic (P) responses, and hence the CIE mesopic system 53 provides the weighting factor according to the level of adaptation and the S/P ratio of lighting, this being established by consensus between the two bodies of work.…”
Section: Developments In Science and Technologymentioning
confidence: 99%
“…54 The mesopic system was derived from two parallel bodies of work, the European MOVE consortium [55][56][57][58] who used and driving on a test track. 62 The mesopic visual response is essentially a weighed combination of the scotopic (S) and photopic (P) responses, and hence the CIE mesopic system 53 provides the weighting factor according to the level of adaptation and the S/P ratio of lighting, this being established by consensus between the two bodies of work.…”
Section: Developments In Science and Technologymentioning
confidence: 99%
“…higher rod stimulation) providing improved detection probability and reaction time. 30,[32][33][34][35][36][37][38] In a recent study, a novel apparatus was built with which to measure detection of pavement obstacles under different light sources and illuminances. 9 The results confirmed that obstacle detection increased with increasing illuminance and with higher S/P ratio ( Figure 3).…”
Section: Obstacle Detectionmentioning
confidence: 99%
“…The 20° size was chosen because the experiments contributing to CIE 191 1 used a 10° offaxis target which falls at the perimeter of this schematic. [11][12][13] We first assumed the whole of this field to be relevant, but also investigated the effect of ignoring the upper part of the field assumed to be less critical for drivers.…”
Section: Estimation Of Peripheral Lbmentioning
confidence: 99%